Rice Ecology and Ecological Relations: An Ontological Analysis of the Jiangjunya Masks and Crop Images from China's East Coast. Issue 4 (November 2019) - Qu, Feng
Abstract : Depictions of human faces and rice-crop images found at the Jiangjunya rock-art site in Lianyungang City, Jiangsu Province, China, reveal entangling relationships between spiritual and economic aspects. Drawing on the relational ecology model and animist ontology theory, the author provides an analysis of the Jiangjunya rock art in its economic, social, spiritual and historical contexts, proposing that prehistoric farmers along China's east coast perceived rice plants as relating to persons. Rice was conceptualized not in utilitarian terms as a means of subsistence (used and consumed by humans) but rather as subjects capable of action. The human masks of Jiangjunya hence suggest a personhood for rice, rather than representing humans or anthropomorphic gods. Furthermore, the history of the Jiangjunya rock-art site corresponds with the history of local economics. The relational ontologies might have transformed gradually from human–animal interactions in the Late Palaeolithic and Early Neolithic periods to human–plant interactions in Late Neolithic societies. The author concludes that the art site was possibly treated as a mnemonic maintaining interpersonal and intersubjective relationships across thousands of years.